2018
DOI: 10.1016/j.bjid.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm production by clinical isolates of Pseudomonas aeruginosa and structural changes in LasR protein of isolates non biofilm-producing

Abstract: The modeling of the resulting LasR protein showed a conformational change in its structure, suggesting that this might be the reason why these isolates are unable to produce biofilm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 33 publications
7
38
2
4
Order By: Relevance
“…These residues can bind concurrently to cause protein folding, leading to the dimerization of LasR, thus allowing for DNA binding to the promoter and consequent transcriptional activation of QS-controlled genes. Furthermore, Bjarnsholt et al reported that mutations in Tyrosine-56 and Threonine-75 in the lasR protein would impair autoinducer binding since they strongly interact with the autoinducer (33). In contrast, we did not find any mutation in this region, but we found that missense mutations in region Arginine 180 (R180Q) had a damaging effect on protein function; this also reduced the stability of the protein when compared to strain PAO1.…”
Section: Discussioncontrasting
confidence: 62%
“…These residues can bind concurrently to cause protein folding, leading to the dimerization of LasR, thus allowing for DNA binding to the promoter and consequent transcriptional activation of QS-controlled genes. Furthermore, Bjarnsholt et al reported that mutations in Tyrosine-56 and Threonine-75 in the lasR protein would impair autoinducer binding since they strongly interact with the autoinducer (33). In contrast, we did not find any mutation in this region, but we found that missense mutations in region Arginine 180 (R180Q) had a damaging effect on protein function; this also reduced the stability of the protein when compared to strain PAO1.…”
Section: Discussioncontrasting
confidence: 62%
“…In this study, all S. pseudintermedius clinical OE isolates produced biofilm, but 80% of these isolates ( biofilms (Lima et al, 2018). In a study of P. aeruginosa isolates from cases of cystic fibrosis, 68% (n = 74) formed biofilms with the majority (64.9%) being weak biofilm producers (Perez, Costa, Freitas, & Barth, 2011).…”
Section: Discussionmentioning
confidence: 57%
“…This contrasts with a similar study by Pye et al () in which only 40% (33/83) of P. aeruginosa canine otic isolates produced biofilms (8.4% (7/83) weak, 18.1% (15/83) moderate and 13.3% (11/83) strong). In humans, the majority (77.5%) of P. aeruginosa isolates formed weak (42.5%), moderate (27.5%) or strong (5%) biofilms (Lima et al, ). In a study of P. aeruginosa isolates from cases of cystic fibrosis, 68% ( n = 74) formed biofilms with the majority (64.9%) being weak biofilm producers (Perez, Costa, Freitas, & Barth, ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous external factors affect biofilm formation by Pseudomonas aeruginosa. In addition, the type of tissue has strong impact on biofilm formation, and researchers commonly test biofilm formation of Pseudomonas aeruginosa from a variety of clinical sources [41]. In our study, various clinical strains showed differences in sensitivity to tested compounds, but those variations were not connected to specific bacterial source (urine, ear swab, sputum).…”
Section: Discussionmentioning
confidence: 76%